The happening - Shyamalan, M. Night; Mercer, Sam; Mendel, Barry ([Beverly Hills, Calif..] : Twentieth Century Fox, 2008)
An unstoppable event threatens the world's population by attacking the most basic human instinct of all: survival. Elliot Moore is an ordinary man who is trying to save his family from a terrifying, invisible killer. As Elliot discovers the incredible possibility of what is happening, it becomes very clear that no one is safe
Cast: Mark Wahlberg, Zooey Deschanel, John Leguizamo, Betty Buckley
DVD format
Keywords: Survivalism -- United States -- Drama; Microbial toxins -- Drama; Winds -- United States -- Drama; Mass suicide -- United States -- Drama